Triceratops : the last dinosaur - Sandell, Elizabeth J.; Oelerich, Marjorie L. (Mankato, MN, U.S.A. : Bancroft-Sage Pub., 1988)
Presents presently-known information on the plant-eating dinosaur that looked like a rhinoceros.
Keywords: Triceratops; Triceratops; Dinosaurs